Technological change and the dynamics of industries : theoretical issues and empirical evidence from Dutch manufacturing - Van Dijk, Machiel (Amsterdam ; Boston : North-Holland/Elsevier, 2002)
Focuses on variances in the structural and dynamic properties of manufacturing industries. By exploring the theoretical and empirical literature in industrial economics, by using a longitudinal firm-level database, and by developing and simulating a model on industrial dynamics, the following results are shown. Empirically, both the technological regime framework as well as the product or industry life cycle approach can explain differences between industries. Theoretically, it is shown that the differences in the timing and frequency of new technology adoptions provide an additional explanation for the structural and dynamic differences between industries.
Includes bibliographical references and index.
oif 08/08/16
Loan
Keywords: Manufacturing industries; Mathematical models; Technological innovations; Industrial organization (Economic theory); Netherlands